What does Williams syndrome reveal about the determinants of social behavior? - Järvinen, Anna M.; Bellugi, Ursula (Frontiers in Human Neuroscience, 2013)
Growing evidence on autonomic nervous system (ANS) function in individuals with Williams syndrome (WS) has begun to highlight aberrancies that may have important implications for the social profile characterized by enhanced social motivation and approach. In parallel, neurobiological investigations have identified alterations in the structure, function, and connectivity of the amygdala, as well as prosocial neuropeptide dysregulation, as some of the key neurogenetic features of WS. A recent social approach/withdrawal hypothesis (Kemp and Guastella, 2011) suggests that autonomic cardiac control may play a key role in regulating the relationship between oxytocin and social behavior. This article discusses evidence from these critical, new strands of research into social behavior in WS, to consider the extent to which data on WS may provide novel insight into the determinants of social behavior. Future research directions are suggested.